The Plate-Washing Assay: A Simple Test for Filamentous Growth in Budding Yeast - Cullen, Paul J. (Cold Spring Harb Protoc, 2015)
Filamentous growth is a foraging response that occurs in fungal species. It allows fungal pathogens to invade cells and tissues of a host organism. Budding yeast undergoes filamentous growth and can invade semisolid agar plates, penetrating the agar surface. These cells cannot be removed by rinsing with water, and form an invasive scar. The plate-washing assay is an easy first test for filamentous growth and is performed at low cost with minimal reagents. The assay is versatile: it can be used as a teaching tool, is amenable to high-throughput genetic analysis, and is used to evaluate filamentous growth in different fungal species including pathogens like Candida albicans.